PENGARUH BRAND IDENTIFICATION, SELF-IMAGE EXPRESSION, SENSE OF NATURAL ENVIRONMENT, LAYOUT, BRAND LOVE TERHADAP BRAND LOYALTY PADA RESTORAN SUSHI TEI - Wina Cita Yunita; Margaretha Pink Berlianto (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
The development in the food industry in Indonesia is very fast, even though there are obstacles, namely the COVID-19 pandemic has no effect on the food industry in Indonesia. This research was conducted with the aim of finding a positive relationship related to brand identification with brand love, brand identification with brand loyalty, self-image expression with brand love, sense of natural environment with brand love, layout with brand love, brand love with brand loyalty. The approach in this study is a quantitative approach, the data obtained through the method of collecting data by distributing electronic questionnaires in the form of Google Forms which were distributed to 40 people for preliminary studies and 350 respondents for actual research. The data that has been obtained is processed using SmartPLS. This research was conducted in Indonesia and the respondents who answered the questionnaire were those who had visited the Sushi Tei restaurant. The results of this study indicate thatBAHASA INDONESIA ABSTRACTPerkembangan di industry makanan di Indonesia sangat pesat walaupun adanya hambatan yaitu pandemic covid-19 tidak berpengaruh pada industry makanan di Indonesia. Penelitian ini dilakukan memiliki tujuan yaitu menemukan hubungan positif yang berkaitan dengan brand identification dengan brand love, brand identification dengan brand loyalty, self-image expression dengan brand love, sense of natural environment dengan brand love, layout dengan brand love, brand love dengan brand loyalty. Pendekatan pada penelitian ini adalah pendekatan kuantitatif, data yang didapat melalui metode mengumpulkan data dengan cara menyebarkan kuesioner elektronik berupa Google Forms yang disebarkan kepada 40 orang untuk studi pendahuluan dan 350 responden untuk penelitian actual. Data yang telah diperoleh diolah datanya menggunakan SmartPLS. Penelitian ini dilakukan di Indonesia dan responden yang menjawab kuesioner adalah mereka yang pernah mengunjungi restaurant Sushi Tei. Hasil dari penelitian ini menunjukkan bahwa